2018
DOI: 10.1126/sciadv.aar6849
|View full text |Cite
|
Sign up to set email alerts
|

Genes for de novo biosynthesis of omega-3 polyunsaturated fatty acids are widespread in animals

Abstract: Multiple invertebrates possess enzymes enabling de novo biosynthesis of essential omega-3 fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
267
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(299 citation statements)
references
References 40 publications
(77 reference statements)
11
267
1
Order By: Relevance
“…Consumers have recently been found to be capable of the de novo biosynthesis of long-chained PUFAs (Kabeya et al, 2018), but little is known about the efficiency of this route and the costs involved. Consumers have recently been found to be capable of the de novo biosynthesis of long-chained PUFAs (Kabeya et al, 2018), but little is known about the efficiency of this route and the costs involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers have recently been found to be capable of the de novo biosynthesis of long-chained PUFAs (Kabeya et al, 2018), but little is known about the efficiency of this route and the costs involved. Consumers have recently been found to be capable of the de novo biosynthesis of long-chained PUFAs (Kabeya et al, 2018), but little is known about the efficiency of this route and the costs involved.…”
Section: Discussionmentioning
confidence: 99%
“…It is still largely unknown to what extent the fatty acid composition found in the diet is reflected in the consumers. Consumers have recently been found to be capable of the de novo biosynthesis of long-chained PUFAs (Kabeya et al, 2018), but little is known about the efficiency of this route and the costs involved. For example, Guo et al (2016) indicated different capacities in this respect between a mayfly and a caddisfly species.…”
Section: Discussionmentioning
confidence: 99%
“…Essential fatty acids generally cannot be synthesised de novo by consumers in sufficient quantities to meet their needs (Brett & Mülller-Navarra, 1997;Vance & Vance, 2008); however, recent studies have observed the presence of specific desaturases that support the synthesis of ω-3 (n-3) unsaturated fatty acids from saturated ones in several lineages of invertebrates (Kabeya et al, 2018). fatty acids with more than two double bonds in their C chain) that are involved in maintaining cell structure, metabolism, growth and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…fatty acids with more than two double bonds in their C chain) that are involved in maintaining cell structure, metabolism, growth and reproduction. Essential fatty acids generally cannot be synthesised de novo by consumers in sufficient quantities to meet their needs (Brett & Mülller-Navarra, 1997;Vance & Vance, 2008); however, recent studies have observed the presence of specific desaturases that support the synthesis of ω-3 (n-3) unsaturated fatty acids from saturated ones in several lineages of invertebrates (Kabeya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additional well-annotated crustacean sequences found to be most closely related to each 197 of the P. littoralis transcripts through blastx were added to the alignment. We also included putative desaturase 198 and elongase genes from the hydrozoan Hydra vulgaris and two w-end desaturase sequences from the copepods 199 Lepeophtheirus salmonis and Caligus rogercresseyi (27). For each gene family, an unrooted maximum likelihood…”
mentioning
confidence: 99%